Pinnacle Rock from aboard the steamboat PROSPECTOR, travelling up the Pelly River, Yukon Territory, August 1901. - Meed, William E.
PH Coll 246.262 Photographs taken on trip by the steamboat PROSPECTOR in August 1901. It was the first navigation of the Pelly and MacMillan Rivers by a steamboat. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number